Theory and Practice: a Different Approach to ESP Testing (Training and Practice : Journal of Educational Sciences, 2007)
The explosion of the second industrial and scientific revolution in the 20th century has caused English to become the ‘lingua franca’ of the international community. English language became a natural link within multi-cultural, multilingual societies and a vehicle for international communication. As a result of the above mentioned social, economic, technological and scientific changes teaching and testing ESP have been improving all over the world. We see ESP movement all around us in colleges and universities (English for Academic Purposes) and in adult schools (English for Occupational Purposes) as well. ESP testing is largely addressed to adult learners and university students who require English language competence to further their education or to perform a social or working role.The first part of the study gives the scientific classification of foreign language testing then a short overview of the history of ESP testing. The author reviews the development of several ESP testing theories and analyzes the precise definition of specific purpose testing as communicative language testing on the basis of the concept of specific purpose language ability. Then the characteristics of communicative general English language testing and communicative ESP testing are compared and contrasted.The last part of the paper focuses on the role of needs-analysis in ESP setting. Needs-assessment has evolved through different phases of development as a highly valid and authentic characteristic of ESP testing, and seen as the foundation of ESP testing on which all other decisions (planning, realisation, and assessment) are, or should be, made.Finally the author reports on an ongoing empirical research (needs-analysis) which aimed to explore the changing needs and objectives of ESP students studying in the Hungarian higher education in the field of social sciences.